Epidemiological characteristics of injury in 7–22-year-old badminton players by age and sex - Xiao Zhou; Kazuhiro Imai; Xiao-Xuan Liu; Zhuo Chen; Eiji Watanabe; Hongtao Zeng (Scientific Reports)
Abstract Badminton-related injury is thought to happen with increasing incidence among badminton players. Literature shown injury incidence across age is scarce. The objective was to investigate the epidemiological characteristics of badminton-related injuries among badminton players broken down by age and sex. This epidemiology study is a retrospective design in 7–22-year-old badminton players at a national competitive tournament with a questionnaire from 2018 to 2023. An injury was defined as somatic complaint with time loss and/or medical care. Badminton-related injuries were normalized to rate per 1000 training-hours calculated by Poisson distribution in the collected data according to age and gender. Among all the 711 badminton players, 60.3% (429 players) suffered from at least one badminton-related injury. Regardless of gender, the most frequently injured anatomical site was knee (male: 18.8%, female: 18.6%), followed by ankle (male: 13.4%, female: 13.4%) and lower back (male: 12.3%, female: 10.0%). In male badminton players, the shoulder (7.6%) ranked fourth as the plantar (6.7%) ranked fourth in female badminton players. The rate per 1000 training-hours of badminton-related injuries showed that male players peaked at age 15–16 years and female players peaked at age 17–18 years, with 3.24 injuries and 3.52 injuries per 1000 training-hours, respectively. In 7–22-year-old badminton players, knee, lower back, and shoulder injuries frequently occurred and were significantly associated with the incidence of badminton-related injuries. The peak incidence of badminton-related injuries was in 15–16-year-old male badminton players while the peak incidence was in 17–18-year-old female badminton players. These data have the potential to help target the most at-risk anatomical sites and the most at-risk badminton players precisely for injury prevention programs.